Isoprenoid alcohols utilization by malaria parasites - Bofill Verdaguer, Ignasi; Sussmann, Rodrigo A. C.; Santiago, Verônica Feijoli; Palmisano, Giuseppe; Moura, Gabriel Cândido; Mesquita, Juliana Tonini; Yamaguchi, Lydia Fumiko; Kato, Massuo Jorge; Katzin, Alejandro Miguel; Crispim, Marcell (Frontiers in Chemistry, 2022)
Plasmodium falciparum is the etiological agent of human malaria, one of the most widespread diseases in tropical and subtropical regions. Drug resistance is one of the biggest problems in controlling the disease, which leads to the need to discover new antimalarial compounds. One of the most promissory drugs purposed is fosmidomycin, an inhibitor of the biosynthesis of isoprene units by the methylerythritol 4-phosphate (MEP) pathway, which in some cases failed in clinical studies. Once formed, isoprene units are condensed to form longer structures such as farnesyl and geranylgeranyl pyrophosphate, which are necessary for Heme O and A formation, ubiquinone, and dolichyl phosphate biosynthesis as well as for protein isoprenylation. Even though the natural substrates of polyprenyl transferases and synthases are polyprenyl pyrophosphates, it was already demonstrated that isoprenoid alcohols (polyprenols) such as farnesol (FOH) and geranylgeraniol (GGOH) can rescue parasites from fosmidomycin. This study better investigated how this rescue phenomenon occurs by performing drug-rescue assays. Similarly, to FOH and GGOH, it was observed that phytol (POH), a 20-carbon plant isoprenoid, as well as unsaponifiable lipid extracts from foods rescue parasites from the antimalarial effect of fosmidomycin. Contrarily, neither dolichols nor nonaprenol rescue parasites from fosmidomycin. Considering this, here we characterized the transport of FOH, GGOH, and POH. Once incorporated, it was observed that these substances are phosphorylated, condensed into longer isoprenoid alcohols, and incorporated into proteins and dolichyl phosphates. Through proteomic and radiolabelling approaches, it was found that prenylated proteins are naturally attached to several isoprenoids, derived from GGOH, dolichol, and POH if exogenously added. Furthermore, the results suggest the presence of at least two promiscuous protein prenyltransferases in the parasite: one enzyme which can use FPP among other unidentified substrates and another enzyme that can use GGPP, phytyl pyrophosphate (PPP), and dolichols, among other substrates not identified here. Thus, further evidence was obtained for dolichols and other isoprenoid products attached to proteins. This study helps to better understand the apicoplast-targeting antimalarial mechanism of action and a novel post-translational modification of proteins in P. falciparum.